Education for sustainable development: An evaluation of students' perceptions within the Bucharest University of Economic Studies - Grigore Ioan Pirosca; George-Lauretiu Serban-Oprescu; Liana Badea; Silvia Dedu (Amfiteatru Economic Journal, 2020)
Education for sustainable development (ESD) is a key component of sustainable university. The complex issue of ESD raised a great amount of interest among scholars and stakeholders. The body of studies published so far highlight that even though ESD seems well defined from a theoretical level, there are still numerous gaps and missing links between university policies and strategies. In this context, the present study explores how business students, as recipients of ESD, perceive their own level of knowledge acquired about sustainable development. Using statistical and econometric methods on a sample (N = 1249) of students from Bucharest University of Economic Studies (which is the most important university in Romania on the economic field), the study shows a heterogeneous perception among observed population. Bucharest University of Economic Studies (BUES) was chosen due to the fact that it is the most prestigious university in Romania, ranking 801-1000 in the world in the Times Higher Education World University Ranking 2020 and thus being ranked first in Romania. Also, the significant number of students enrolled in the bachelor's degree (27,598) places BUES among the largest universities with economic and business profile in the South-East of Europe. The results of the research show a heterogeneous perception in the analyzed sample and reveals university studies potential to develop ESD (the students in the final year report a higher level of knowledge on sustainable development than those in the first year). At the same time, students perceive a level of knowledge acquired about sustainable development below average, which suggests that ESD among business students is still at an early stage. Finally, the analysis shows that, frequently, students are not fully aware that the information gained during university studies is relevant to the issue of sustainable development.
Keywords: Q01; I25; A20; 330; education for sustainable development; sustainable university; objectives of sustainable development; Bucharest University of Economic Studies